Profil Berpikir Kritis Matematis Siswa SMP Ditinjau dari Gaya Kognitif - Lestari, Revita Dwi; Koesharyanti, Nabila Dwi; Hidayah, Nafisatul; Nurfiyani, Okta; Setiyani, Linda Dewi; Sutrisno, Sutrisno (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
This study investigates the critical thinking profiles of junior high school students based on their cognitive styles, Field Independent (FI) and Field Dependent (FD), within the context of solving contextual geometry problems. Critical thinking is an essential component of 21st-century mathematics learning, yet national and international assessments indicate that Indonesian students still struggle to demonstrate higher-order reasoning, particularly in geometry. To explore how cognitive style shapes students’ thinking processes, this study employed a descriptive qualitative approach involving four eighth-grade students selected purposively, consisting of two FI and two FD students determined using the GEFT. Data were collected through contextual geometry tests, task-based interviews, documentation, and field notes. The data were analyzed using Miles, Huberman, and Saldaña’s interactive model with support from NVivo for qualitative coding. Findings show that FI students produced higher and more consistent coding frequencies on the indicators of interpretation, analysis, evaluation, and explanation, and displayed more structured reasoning. In contrast, FD students demonstrated limited elaboration, intuitive responses, and lower coding frequencies. These results confirm that cognitive style significantly influences the depth of critical thinking. The study implies the need for differentiated mathematics instruction that accommodates students’ cognitive profiles to enhance critical thinking in geometry learning.